Enhanced coagulation of low-turbidity micro-polluted surface water: Properties and optimization. (1st March 2019) - Liu, Zhouzhou; Wei, Hua; Li, Aimin; Yang, Hu
Abstract: Micro-polluted surface water with low turbidity and low content of dissolved organic matter (DOM) is usually inefficiently purified. In this work, a combined technique for the enhanced coagulation of this surface water was proposed and investigated using cationic grafted starch (St-G) and polyaluminum chloride (PACl) as co-coagulants, followed by a magnetic ion-exchange resin (MIER). St-G was fed before PACl, and this procedure not only efficiently removes turbidity but also largely reduces the doses of the two coagulants. MIER remarkably removed DOM, and raw water was effectively purified. The entire coagulation process was further optimized through response surface methodology based on a central composite design by using the doses of St-G, PACl, and MIER as input variables. The dose effects of the three chemicals on the coagulation performance for turbidity and DOM removal were examined, and the coagulation mechanisms, including the interactive effect among various chemicals, were discussed in detail. This work provided a new strategy for the efficient treatment of low-turbidity micro-polluted surface water by utilizing organic and inorganic co-coagulants with magnetic ion-exchange resin in practical applications. Graphical abstract: Image 1 Highlights: Enhanced coagulation of micro-polluted surface water with low turbidity and low COD. Enhanced coagulation using co-coagulants followed by magnetic ion-exchange resin. A cationic graft starch (St-G) and PACl used as co-coagulants and PACl fed after St-G. Optimization of this enhanced coagulation process using response surface method (RSM). Discussion of the complementary mechanisms from experimental data and RSM analysis.